1992
DOI: 10.1111/j.1439-0434.1992.tb01248.x
|View full text |Cite
|
Sign up to set email alerts
|

Etiology and Transmission of Sesame Phyllody in Iran

Abstract: Phyllody is a destructive disease of sesame (Sesamum indicum L.) in Iran. The major symptoms of the disease are floral virescence, phyllody and proliferation. Other symptoms which sometimes accompany the disease are yellowing, cracking of seed capsules, germination of seeds in the capsules and formation of dark exudates on the foliage. Light microscopy of hand‐cut sections of sesame and colza (Brassica napus L. cv. Oro) stems treated with Dienes' stain showed blue areas in the phloem region of phyllody infecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
30
1

Year Published

1997
1997
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(36 citation statements)
references
References 9 publications
5
30
1
Order By: Relevance
“…This result indicated that Sesamum phyllody was transmitted to 80 per cent of the graft transmitted plants (Table 4). Similar observations were also reported by Salehi et al, (1992), Akhtar et al, (2009) and Pathak et al, (2012). The Phytoplasmas move within plants through the phloem from source to sink and they are able to pass through sieve tube elements in phloem tissues (Christensen et al, 2004).…”
Section: Graft Transmissionsupporting
confidence: 80%
See 1 more Smart Citation
“…This result indicated that Sesamum phyllody was transmitted to 80 per cent of the graft transmitted plants (Table 4). Similar observations were also reported by Salehi et al, (1992), Akhtar et al, (2009) and Pathak et al, (2012). The Phytoplasmas move within plants through the phloem from source to sink and they are able to pass through sieve tube elements in phloem tissues (Christensen et al, 2004).…”
Section: Graft Transmissionsupporting
confidence: 80%
“…Similarly many other workers could also successfully transmit the disease from infected plant to healthy plant with the help of dodder (Salehi and Izadpanah, 1992;Akhtar et al, 2009 andPathak et al, 2012). Marcone et al, (1997) reported successful dodder transmission of alder yellows phytoplasma to the experimental host Catharanthus roseus (periwinkle).…”
Section: Dodder Transmissionmentioning
confidence: 99%
“…However, in Pakistan, some other symptoms were observed which include longitudinal splitting of pods and germination of physiologically mature green seeds within these pods. Germination of seeds in nature due to phytoplasma-infection have earlier been found in capsules of International Journal of Pest Management 143 sesame in Iran and Pakistan (Salehi and Izadpanah, 1992;Akhtar et al 2009a) and in pods of chickpea in Pakistan (Akhtar et al 2009b). Seed transmission of pathogens poses a risk of long distance disease spread (van Vuuren et al 2011).…”
Section: Discussionmentioning
confidence: 96%
“…Insect vectors feeding from phloem sap mainly leafhoppers (Cicadellidae) and planthoppers (Fulgoromorpha) and psyllids (Psyllidae), play a major role in their transmission to plant hosts (Lee et al, 2000;Garnier et al, 2001;Weintraub and Beanland, 2006). In detection of phytoplasmal diseases, symptomatology, serology and microscopy techniques were employed in early detection methods (Salehi and Izadpanah, 1992;Kersting, 1993;Klein, 1997;Seemüller et al, 1998;Firrao et al, 2007). After development of molecular techniques, PCR-based methods were routinely used mostly based on the amplification of 16SrRNA genes with nested PCR with phytoplasma specific primers (Ahrens and Seemüller, 1992;Gundersen and Lee, 1996;Smart et al, 1996).…”
Section: Introductionmentioning
confidence: 99%